Benefits and shortcomings of utilizing telemedicine during the COVID-19 pandemic. Issue 4 (1st October 2020) - Burroughs, Mark; Urits, Ivan; Viswanath, Omar; Simopoulos, Thomas; Hasoon, Jamal
Abstract: As the COVID-19 pandemic overwhelmed health care systems around the world, new strategies to mitigate its spread and provide patients access to health care have been employed. Although a critical component of this strategy, telemedicine is not a perfect solution for many scenarios and is often limited. Overall, telemedicine has been an invaluable tool to improve access to care and minimize the risk of person-to-person transmission of COVID-19.